Thermal Decomposition Kinetic Studies of Some Metal Complexes - Bhartiya, S.K.; Yadav, S.P. (Asian Journal of Chemistry, 2016)
Thermogravimetric analysis was used to determine kinetic parameters such as order of reaction, activation energy, frequency factor etc. of some metal complexes based on the method of Freeman and Carroll.